Ergodicity of the mapping class group action on Deroin-Tholozan representations - Maret, Arnaud (Groups, geometry, and dynamics, 2022)
This note investigates the dynamics of the mapping class group action on compact connected components of relative character varieties of surface group representations into PSL(2, R), discovered by Deroin and Tholozan. We apply symplectic methods developed by Goldman and Xia to prove that the action is ergodic.